1998
DOI: 10.1164/ajrccm.157.1.9702093
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profiles and Breathlessness Perception in Outpatients with Different Gradings of Asthma

Abstract: We studied the relationship between personality profiles, breathlessness perception and clinical and functional features in 36 outpatient asthmatics (12 females; age range: 18-52 yr). Each patient underwent psychometric evaluation with Minnesota Multiphasic Personality Inventory (MMPI). Breathlessness perception was evaluated by Borg's scale during methacholine (M) challenge, and PS20 (the perception score obtained when FEV1 fell by 20%) was recorded. Baseline FEV1 values ranged from 70.0 to 126%. PC20 M value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 29 publications
(38 reference statements)
8
53
0
2
Order By: Relevance
“…Most studies performed on adults have shown that poor perceivers were not charac-terized as a distinct group based on gender, age or baseline FEV 1 (1,3,14,24,26). These findings were confirmed in children by Fritz et al (11) and in our study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Most studies performed on adults have shown that poor perceivers were not charac-terized as a distinct group based on gender, age or baseline FEV 1 (1,3,14,24,26). These findings were confirmed in children by Fritz et al (11) and in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Apter et al (1) reported that patients with lower forced expiratory flow between 25% and 75% of the vital capacity (FEF ) tended to be less accurate perceivers. Chetta et al (24) found that poor perception was associated with asthma severity and Bijl-Hofland et al (25) reported that low baseline forced expiratory volume in 1 s (FEV 1 ) and high hyperresponsiveness were associated with a low perceptiveness of bronchoconstriction. In contrast, Pfeiffer et al (14) concluded that good and poor perceivers did not differ in terms of the severity or duration of asthma and Fritz et al (11) reported that children s perceptual accuracy of symptoms was not related to severity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a weak correlation between symptoms on the one hand and bronchial hyperresponsiveness and airways inflammation on the other. Several investigators have highlighted the possibility of diminished perception of dyspnoea in subjects with more severe grades of asthma, potentially leading to undertreatment in these subjects [7][8][9]. Such an inverse relationship is not a consistent finding [10].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between dyspnoea perception and other indices of asthmatic severity, such as the degree of bronchoconstriction, is poor [5,6]. Conversely, impaired dyspnoea perception is especially believed to play a role in severe asthma [7][8][9]. Poor perception of airflow obstruction may lead to undertreatment of asthma [10].…”
mentioning
confidence: 99%
“…(7) Although patients with stable asthma always recognize an increase in the degree of dyspnea due to induced bronchospasm, there is a wide range in the magnitude of dyspnea perception for the same value of FEV 1 . (7,8) It has been suggested that this variability is attributable to certain pathophysiological and psychological factors. (9) To determine the level of dyspnea perception, various types of scales have been devised, including visual analog scales, verbal category scales, and hybrid scales.…”
Section: Introductionmentioning
confidence: 99%